Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd006681.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Low molecular weight heparin for prevention of venous thromboembolism in patients with lower-leg immobilization

Abstract: Use of LMWH in outpatients significantly reduces VTE when immobilization of the lower leg is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 41 publications
1
33
0
1
Order By: Relevance
“…The incidence of symptomatic VTE in our study among foot and ankle patients undergoing below-knee immobilization for non-operative injury falls well within the wide range of findings from previous studies, which themselves ranged from 0.0% to 17.3%. [4][5][6][7][8][9][10][11][12][13][14] The largest retrospective study of which we are aware included 14,777 patients treated non-operatively for an ankle fracture and demonstrated a rate of symptomatic VTE of 0.22%. Two smaller studies involving 200 and 150 patients treated non-operatively for foot and ankle fractures found 1 (0.5%) symptomatic DVT and 3 (2%) symptomatic VTE respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of symptomatic VTE in our study among foot and ankle patients undergoing below-knee immobilization for non-operative injury falls well within the wide range of findings from previous studies, which themselves ranged from 0.0% to 17.3%. [4][5][6][7][8][9][10][11][12][13][14] The largest retrospective study of which we are aware included 14,777 patients treated non-operatively for an ankle fracture and demonstrated a rate of symptomatic VTE of 0.22%. Two smaller studies involving 200 and 150 patients treated non-operatively for foot and ankle fractures found 1 (0.5%) symptomatic DVT and 3 (2%) symptomatic VTE respectively.…”
Section: Discussionmentioning
confidence: 99%
“…3 In contradistinction, a recent Cochrane meta-analysis alternatively concluded that patients treated non-operatively with lower-leg immobilization demonstrate a heightened risk of VTE-and recommended the routine use of chemoprophylaxis. 4 Notably, such studies demonstrated sizeable variability in VTE incidence, ranging from 0.0% to 17.3%, [4][5][6][7][8][9][10][11][12][13][14] possibly stemming from variations in patient risk factors. [7][8][9] This high variability in VTE incidence suggests that specific subpopulations of patients who present with foot or ankle injury may be at heightened risk of VTE, and may therefore benefit from chemoprophylaxis when undergoing below-knee immobilization.…”
mentioning
confidence: 99%
“…Many risk factors for venous thrombosis have been identified, both genetic and environmental [8,9]. One of these known risk factors is cast immobilization, especially immobilization of the lower extremity [10,11]. However, the exact size of the risk attributable to lower leg cast immobilization is not known.…”
Section: Introductionmentioning
confidence: 99%
“…While the risk for clinically relevant thrombosis in a cast is not clearly established, imaging studies suggest a rate between 4.3% and 40%, 15 so prophylaxis should be considered. Whether prophylaxis should be universal, or solely for those with identifiable risk factors, is controversial.…”
Section: Introductionmentioning
confidence: 99%
“…The most suitable prophylaxis has not been established: a chemical agent can be given for the time in plaster, for which there is some evidence of effect. 1,15 Mechanical methods would be more suitable for those with a risk of bleeding, particularly soon after injury or surgery; however, traditional mechanical methods are not practical for those in a plaster cast.…”
Section: Introductionmentioning
confidence: 99%